Verbal Fluency according to task type, time interval and socioeconomic status in school-aged children - Arán Filippetti, Vanessa (Anales de Psicología / Annals of Psychology, 2011)
The aim of this study was to analyze verbal fluency (VF) according to task type (semantic vs. phonologic), time interval (1-15seg. vs. 16-30seg. vs. 31-45seg. vs. 46-60seg.) and socioeconomic status (medium vs. low) in school-aged children. The sample included 248 children aged between 8 and 12 years from different socioeconomic status (SES). Semantic and phonological VF tests and other cognitive tasks were administered in order to evaluate possible associations. The results indicated significant differences according to SES as regards the total number of words generated in both VF tasks and as a function of time. Children from lower socioeconomic status had demonstrated more difficulty in generating words in the phonological task, and since the 16 seconds where controlled processes are at stake. In addition, the relationship between different socioeconomic variables and VF was analyzed, and it was found that the level of instruction of the mother was the only significant predictor. Finally, the results revealed that language, intelligence and other executive functions predict VF performance, despite differences in terms of semantic or phonologic tasks. The results are discussed considering the usefulness of the task as a measure of cognitive processing and the impact that SES has on controlled processing and executive functioning.